The asymmetric effect of oil price fluctuation on non-performing loans in Kazakhstan: evidence from the ricardian curse of the resource boom - Chin, Lee; Saydaliev, Hayot Berk; Kadyrov, Shirali (Taylor and Francis, 2022)
This paper investigates the asymmetric impact of oil price fluctuations on non-performing loans (NPLs) between 2009-Q1 and 2020-Q1 for 28 banks in Kazakhstan. Dynamic panel threshold analysis revealed an initial increase of oil prices, improving creditworthiness, thereby reducing NPLs; however, after cross a certain threshold, the relationship was shown to become the opposite. This finding is in line with the Ricardian curse and resource windfall. The results suggest that optimal borrowings and lending should be actively monitored to mitigate potential liquidity problems of banks and consequently NPLs. The practical implications and policy recommendation of which are important to policy makers.